Secure and optimized satellite image sharing based on chaotic eπ map and Racah moments - Karmouni, Hicham; Tahiri, Mohamed Amine; Dagal, Idriss; Amakdouf, Hicham; Jamil, Mohamed Ouazzani; Qjidaa, Hassan; Sayyouri, Mhamed (PERGAMON-ELSEVIER SCIENCE LTD, 2024)
The objective of this paper is to contribute to the sharing, transfer, and secured indexing of large color images. Watermarking and digital encryption have emerged as alternative and complementary solutions to ensure authorized access, facilitate authentication of content, or prevent illegal reproduction. For this reason, we suggest a new system based on four techniques derived from various transformation and decomposition methods, such as the discrete orthogonal Racah moment transformations (DORMT), which allows the information capacity to be reduced to a number of coefficients, as well as the discrete wavelet transform (DWT), which makes it possible to decompose into a certain number of multilevel sub-bands, to have the sub-band that represents most of the image information. In addition, Schur decomposition (SD) and singular value decomposition (SVD) have been used to increase security. The proposed system consists of two main phases. The first phase is the integration of a color watermark, first applying DORMT-SD-SVD to a color host image and then applying DWT-SD-SVD to achieve a compromise between capacity, invisibility and robustness in terms of quality and privacy. The second phase is the encryption of the watermarked image with an e pi map to increase security for sharing, transfer and indexing. This system uses an Aquila Optimization Algorithm (AOA) as an optimization procedure to find the best set of DORMT parameters and provide a dynamic and adaptive scale factor. The experimental results, in which the proposed system's properties are tested and compared to those of other systems, make it clear that the proposed system is useful in terms of its level of security, capacity, invisibility, and resistance to attacks that use signal processing.
Keywords: Racah moments; Sohur decoposition; Singular value decomposition; kDiscrete wavelet transform; aquila optimization algorithm; COLOR IMAGES; WATERMARKING; ALGORITHM; ROBUST; SVD; RECONSTRUCTION; TRANSFORM; Computer Science; Engineering; Operations Research & Management Science